Calibration of sea ice dynamic parameters in an ocean‐sea ice model using an ensemble Kalman filter. Issue 7 (8th July 2014) - Massonnet, F.; Goosse, H.; Fichefet, T.; Counillon, F.
Abstract The choice of parameter values is crucial in the course of sea ice model development, since parameters largely affect the modeled mean sea ice state. Manual tuning of parameters will soon become impractical, as sea ice models will likely include more parameters to calibrate, leading to an exponential increase of the number of possible combinations to test. Objective and automatic methods for parameter calibration are thus progressively called on to replace the traditional heuristic, "trial‐and‐error" recipes. Here a method for calibration of parameters based on the ensemble Kalman filter is implemented, tested and validated in the ocean‐sea ice model NEMO‐LIM3. Three dynamic parameters are calibrated: the ice strength parameter P*, the ocean‐sea ice drag parameter Cw, and the atmosphere‐sea ice drag parameter Ca. In twin, perfect‐model experiments, the default parameter values are retrieved within 1 year of simulation. Using 2007–2012 real sea ice drift data, the calibration of the ice strength parameter P* and the oceanic drag parameter Cw improves clearly the Arctic sea ice drift properties. It is found that the estimation of the atmospheric drag Ca is not necessary if P* and Cw are already estimated. The large reduction in the sea ice speed bias with calibrated parameters comes with a slight overestimation of the winter sea ice areal export through Fram Strait and a slight improvement in the sea ice thickness distribution. Overall, the estimation of parameters with the ensemble Kalman filter represents an encouraging alternative to manual tuning for ocean‐sea ice models.